The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.jsat.2008.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Treatment entry barriers among California's Proposition 36 offenders

Abstract: To explore why some Proposition 36 offenders do not enter drug treatment, we analyzed self-reported and administrative data to compare the characteristics, perceptions, and rearrest rates of 124 untreated and 1,335 treated offenders assessed by 30 sites in five California counties. Offenders were comparable in many domains at assessment; however, untreated offenders were younger, not employed, more criminally severe, and less motivated for treatment. To avoid incarceration was the primary reason for choosing P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…Substance abuse treatment has been shown to result in fewer arrests (Luchansky et al, 2006), lower risk of felony convictions (Luchansky, He, Longhi, Krupski, & Stark, 2006; Luchansky, Nordlund, et al, 2006), declines in self-reported illegal activities (Hubbard, Craddock, & Anderson, 2003), lower re-arrests among clients participating in treatment in lieu of incarceration for drug-related offenses (Evans, Huang, & Hser, 2011), lower conviction rates (Gossop, et al, 2005), and lower arrests for both all types of crimes and specifically property and drug-related crimes (Evans, Li, & Hser, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Substance abuse treatment has been shown to result in fewer arrests (Luchansky et al, 2006), lower risk of felony convictions (Luchansky, He, Longhi, Krupski, & Stark, 2006; Luchansky, Nordlund, et al, 2006), declines in self-reported illegal activities (Hubbard, Craddock, & Anderson, 2003), lower re-arrests among clients participating in treatment in lieu of incarceration for drug-related offenses (Evans, Huang, & Hser, 2011), lower conviction rates (Gossop, et al, 2005), and lower arrests for both all types of crimes and specifically property and drug-related crimes (Evans, Li, & Hser, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…This issue of treatment as a missed opportunity could seriously jeopardize the effectiveness of Prop 36 as a criminal justice diversion option in California, and it highlights the need to identify strategies for improving both policies and programming that guide the Prop 36 program (Little Hoover Commission, 2008). Issues related to the problem of treatment no-shows have been examined elsewhere (Evans et al, in press). Increased understanding of barriers to treatment completion as well as offender attitudes and experiences of treatment dropout are needed to help stakeholders make appropriate modifications to improve the effectiveness of the Prop 36 program.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have documented offender characteristics and treatment needs (Anglin et al, 2007; Brecht, Stein, Evans, Murphy, & Longshore, 2009; Hser et al, 2003; Longshore et al, 2005; Prendergast, Greenwell, Farabee, & Hser, 2009; Urada et al, 2009; Wiley et al, 2004), treatment services utilization and outcomes (Cosden et al, 2006; Evans, Hser, & Huang 2009; Evans, Li, & Hser, 2008; Farabee, Hser, Anglin, & Huang, 2004; Fosados, Evans, & Hser, 2007; Hser, Evans, Teruya, Huang, & Anglin 2007), and cost effectiveness (Hawken, 2008; Longshore, Hawken, Urada, & Anglin, 2006). …”
Section: Introductionmentioning
confidence: 99%